Tariff modulation for the access to the drinking water system as strategies to the water resource safeguard in the Province of Asti (Italy) - Zicari, Giuseppe; Soardo, Vincenzo; Berruti, Renza; Panata, Marisa; Cerrato, Elena (Progress in Nutrition, 2014)
Background: The term “Fare” indicates the payment rate that users must implement to use the service water supply. The Price for drinking water supply distinguishes between a domestic use and other types of use, such as the agricultural or the industrial one, and it is given by the sum of a fixed quota and another proportional to consumption. Method: We compared the fares of different categories of users applied by the Managers of the Water Service operating in the Province of Asti area (Piedmont, Italy), where 222,500 inhabitants live. Results: In the Province of Asti, over 13 Managers of Water Service are active to supply more than 100 water networks and in various municipalities very different prices have been applied: they can vary up to 3-4 times. Generally, the prices applied to households are more than the double of those applied to agricultural and livestock utilities, but at least 80-90 times lower than bottled water prices. In this paper, we examine the prices applied by the different municipalities in the Province of Asti and we propose strategies to modulate the costs on the basis of “efficiency and sustainability” in order to encourage savings and a better use of water resources.